(untitled) (Journal of Oriental Studies, 2017)
The history of military-political strategy of China has deep roots. In general all actions of the People’s Republic of China it is directly connected with its strategic interest. China first of all needs building-up of military potential for strengthening of a superiority in the Pacific Rim. Because exactly there are not solved problems. In article the provision of the Chinese army about the beginning of reforms is considered. In communication developed a situation in the world the government of the People’s Republic of China to set new tasks for army. Forming of modern army, providing with new technologies, advanced training of personnel structure, in a word to have army conforming modern to requirements is the purpose of the Chinese government. And for this purpose it is carried out large-scale works, the international military cooperation also extends.